2022
DOI: 10.1164/rccm.202006-2467oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Increases the Potential for Neutrophil-mediated Endothelial Damage in Chronic Obstructive Pulmonary Disease

Abstract: Scientific knowledge on the subject: COPD is characterised by persistent neutrophilia in the setting of local and systemic hypoxia, and is associated with excess cardiovascular disease, even allowing for known risk factors. Neutrophils accumulating in areas of inflammation and microcirculatory impairment experience profound hypoxia, which prolongs their survival and increases their secretory responses. Thus, hypoxic neutrophils have increased potential to cause endothelial injury but their role in mediating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Through the analysis of immune cell infiltration, it was found that compared with the high expression of WTAP, the low expression group of wtap was significantly higher in neutrophils and eosinophils.It can be concluded that m6A subtype is related to neutrophil extracellular trap (NET) and eosinophil extracellular trap (EET) caused by neutrophils and eosinophils.The clusterB subtype is related to monocyte extracellular trap (MOET) caused by monocytes.EET is composed of DNA fiber network released after activation of eosinophils and granular proteases such as eosinophil cationic protein (ECP) and major basic protein (EOM).Studies have found that activated eosinophils in severe asthma can activate type 2 innate immune lymphocytes through EET to induce steroid resistance [42].Net is a reticular extracellular structure composed of extracellular DNA released by activated neutrophils and neutrophil elastase (NE), myeloperoxidase (MPO) and other degradation enzymes. Studies have shown that enhanced net in COPD patients can be related to airflow restriction and lung tissue injury in COPD patients by activating airway neutrophil inflammation [43].In addition, the study found that MOET can be activated by reactive oxygen species (ROS), showing a similar morphology to net releasing myeloperoxidase (MPO), lactoferrin (LF), elastase and so on, but the release of MOET does not depend on MPO activity [44].Other studies have found that hypoxia can cooperate with inflammatory mediators to promote the release of tissue toxic proteins such as neutrophil elastase (NE), myeloperoxidase (MPO), vascular injury or activated intercellular adhesion molecule (ICAM-1) in COPD to induce endothelial injury [45].Other studies have shown that C5AR1 positive neutrophils can also release inflammatory factors such as IL1 β、 TNF α、ENO1 to promote the growth of breast cancer in patients with breast cancer but m6A methylated WTAP can eliminate this process [46].In addition, leukocyte family chemokine (CXCR1) in COPD patients can bind with ligand IL-8 to activate neutrophil chemotaxis, phospholipase D activation and respiratory burst to induce airflow restriction in COPD patients and promote inflammatory response [47].The global initiative for chronic obstructive pulmonary disease (gold) pointed out that the increased eosinophils in the blood and sputum of COPD patients can not only predict the risk of disease exacerbation, but also predict the effect of glucocorticoid treatment [48].In addition, studies have shown that the increase of blood eosinophils in COPD patients is positively correlated with FeNO value and eosinophils have better lung function performance [49].…”
Section: Discussmentioning
confidence: 99%
“…Through the analysis of immune cell infiltration, it was found that compared with the high expression of WTAP, the low expression group of wtap was significantly higher in neutrophils and eosinophils.It can be concluded that m6A subtype is related to neutrophil extracellular trap (NET) and eosinophil extracellular trap (EET) caused by neutrophils and eosinophils.The clusterB subtype is related to monocyte extracellular trap (MOET) caused by monocytes.EET is composed of DNA fiber network released after activation of eosinophils and granular proteases such as eosinophil cationic protein (ECP) and major basic protein (EOM).Studies have found that activated eosinophils in severe asthma can activate type 2 innate immune lymphocytes through EET to induce steroid resistance [42].Net is a reticular extracellular structure composed of extracellular DNA released by activated neutrophils and neutrophil elastase (NE), myeloperoxidase (MPO) and other degradation enzymes. Studies have shown that enhanced net in COPD patients can be related to airflow restriction and lung tissue injury in COPD patients by activating airway neutrophil inflammation [43].In addition, the study found that MOET can be activated by reactive oxygen species (ROS), showing a similar morphology to net releasing myeloperoxidase (MPO), lactoferrin (LF), elastase and so on, but the release of MOET does not depend on MPO activity [44].Other studies have found that hypoxia can cooperate with inflammatory mediators to promote the release of tissue toxic proteins such as neutrophil elastase (NE), myeloperoxidase (MPO), vascular injury or activated intercellular adhesion molecule (ICAM-1) in COPD to induce endothelial injury [45].Other studies have shown that C5AR1 positive neutrophils can also release inflammatory factors such as IL1 β、 TNF α、ENO1 to promote the growth of breast cancer in patients with breast cancer but m6A methylated WTAP can eliminate this process [46].In addition, leukocyte family chemokine (CXCR1) in COPD patients can bind with ligand IL-8 to activate neutrophil chemotaxis, phospholipase D activation and respiratory burst to induce airflow restriction in COPD patients and promote inflammatory response [47].The global initiative for chronic obstructive pulmonary disease (gold) pointed out that the increased eosinophils in the blood and sputum of COPD patients can not only predict the risk of disease exacerbation, but also predict the effect of glucocorticoid treatment [48].In addition, studies have shown that the increase of blood eosinophils in COPD patients is positively correlated with FeNO value and eosinophils have better lung function performance [49].…”
Section: Discussmentioning
confidence: 99%
“…These results led to a very interesting series of studies (4). Neutrophils from either healthy donors or subjects with non-exacerbating COPD and exposed to severe (0.8% O 2 ) hypoxia for 4 hours released more elastase than neutrophils kept in a normoxic environment (21% O 2 ), but only after brief stimulation with combined PAF and fMLP at the end of the hypoxic period.…”
mentioning
confidence: 99%
“…In this issue of the Journal , Lodge and colleagues (pp. 903–916 ) ask, what does hypoxia do to neutrophil function that injures endothelial cells (ECs) ( 4 )? Their initial studies revealed a variable but significant increase in the cleavage products of NE (neutrophil elastase) and proteinase 3 activity in the plasma of subjects with exacerbating COPD compared with healthy donors.…”
mentioning
confidence: 99%
See 2 more Smart Citations